2008
DOI: 10.1192/bjp.bp.107.041582
|View full text |Cite
|
Sign up to set email alerts
|

DRD2 and ANKK1 genotype in alcohol-dependent patients with psychopathic traits: Association and interaction study

Abstract: The TaqI-A of the ANKK1 gene and the C957T of the DRD2 gene are epistatically associated with psychopathic traits in alcohol-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 36 publications
5
69
2
Order By: Relevance
“…2008). In agreement with our results, research works involving fear‐potentiated startle have demonstrated that individuals high in psychopathy are less affected by peripheral information which competes with goal‐relevant information (Newman et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2008). In agreement with our results, research works involving fear‐potentiated startle have demonstrated that individuals high in psychopathy are less affected by peripheral information which competes with goal‐relevant information (Newman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of ANKK1 Taq IA and DRD2 C957T SNPs was performed as described previously (Ponce et al. 2008). The resulting genotypes for Taq IA were clustered according to the presence of at least one A1 allele (A1+ genotype: heterozygous; A1− genotype: homozygous for the A2 allele).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ponce et al (2008) reported that the two SNPs (-141C Ins/Del) and TaqI A, present on DRD2 gene locus were associated with alcoholism in North Indian population. Studies from South Indian population have reported no association between TaqI A polymorphism and alcoholism.…”
Section: Dopaminementioning
confidence: 99%